Sero-prevalence of hepatitis C virus among patients attending STD clinic in Ibadan, Nigeria (2005)
"In the tropics, hepatitis C virus (HCV) seroprevalence ranges from < 0.2% in whole Africa. A strong association between HCV and hepatitis B surface antigen (HBsAg)-negative chronic liver disease and hepatocellular carcinoma has been described. Hepatocellular carcinoma (HCC) is one of the most common cancers among Africans, and in Nigeria by 1970 the estimated rate was 6.6 per 100,000 populations per annum. Sexual transmission was regarded as a minor cause of HCV, the degree of which has not been properly evaluated in most environments. Since it has been established that sexual transmission is an important mode of acquisition of the infection, we therefore set out to find the seroprevalence of HCV among 95 patients attending sexually transmitted diseases (STD) clinic in University College Hospital, Ibadan, Nigeria with a view to recommending preventive and control measures of HCV in our community. The sera collected from these respondents were used for screening for syphilis using the VDRL test, and for HCV antibodies using the MONOLISA anti-HCV (Sanofi, Pasteur France). Mid-stream urine was collected from all participants, and urethral swabs from all male participants while endocervical and high vaginal swabs were collected from female participants. Ulcer swabs were collected from those with genital ulcers. The prevalence of HCV infection was found to be 37.9% in patients presenting with STDs. This comprised 38.9% of males and 61.1% females. This prevalence rate is very high compared with the rate in the general population and other “high-risk” groups in previous studies in the same environment. Factors associated with HCV infection in this environment include high heterosexuality, high level of education, and previous instrumentations such as in scarifications and termination of pregnancy. Prevention and control of STDs will definitely reduce HCV infection and hence the attendant consequences, particularly hepatocellular carcinoma, in our environment. "